2021
DOI: 10.1002/dvdy.338
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β superfamily co‐receptors in cancer

Abstract: Transforming growth factor‐β (TGF‐β) superfamily signaling via their cognate receptors is frequently modified by TGF‐β superfamily co‐receptors. Signaling through SMAD‐mediated pathways may be enhanced or depressed depending on the specific co‐receptor and cell context. This dynamic effect on signaling is further modified by the release of many of the co‐receptors from the membrane to generate soluble forms that are often antagonistic to the membrane‐bound receptors. The co‐receptors discussed here include TβR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 283 publications
(595 reference statements)
0
41
0
Order By: Relevance
“…Endoglin cannot bind TGF-β itself but does bind TGF-β1 and TGF-β3 when these interact with TGFβR3. Endoglin does not bind to TGF-β2 in any form ( Barbara et al, 1999 ; Pawlak and Blobe, 2021 ). It facilitates the interaction of TGF-β and TGFβR2 with the non-classic type-1 receptor, ACVRL1/ALK1 ( Nogués et al, 2020 ) and leads to a shift from TGF-β/TGFβR1/R2/Smad2/3 to TGF-β/ACVRL1/Smad1/5/8 signaling ( Figure 1-4 ).…”
Section: Transforming Growth Factor-β Signaling: Pathways and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoglin cannot bind TGF-β itself but does bind TGF-β1 and TGF-β3 when these interact with TGFβR3. Endoglin does not bind to TGF-β2 in any form ( Barbara et al, 1999 ; Pawlak and Blobe, 2021 ). It facilitates the interaction of TGF-β and TGFβR2 with the non-classic type-1 receptor, ACVRL1/ALK1 ( Nogués et al, 2020 ) and leads to a shift from TGF-β/TGFβR1/R2/Smad2/3 to TGF-β/ACVRL1/Smad1/5/8 signaling ( Figure 1-4 ).…”
Section: Transforming Growth Factor-β Signaling: Pathways and Mechanismsmentioning
confidence: 99%
“…Effects of TGF-β1 and TGF-β3 on EndMT are mediated by increased TGF-β2 secretion in immortalized human dermal endothelial cells, and knockdown of TGF-β2 blocks TGF-β1/2-induced EndMT ( Sabbineni et al, 2018 ). Interestingly, the affinity of TGF-β1 and TGF-β3 to TGFβR2 is about 200–300-fold higher than that of TGF-β2 ( Pawlak and Blobe, 2021 ). Thus, TGF-β1/3 induced ALK5 signaling might be active at low TGF-β concentrations and drive neoangiogenesis in the presence of endoglin, while TGF-β2 signaling is activate when high concentrations of TGF-β2 out-compete TGF-β1/3-binding to TGFβR2.…”
Section: Transforming Growth Factor-β Signaling In Tumorsmentioning
confidence: 99%
“…These zebrafish defects are attenuated with injection of mouse Tdgf1 mRNA underscoring the high level of conserved functionality between these orthologs [ 9 ]. The effects of these orthologs during early gastrulation are driven through their defined roles as essential co-receptors that facilitate binding of a subset of TGF-β superfamily members including NODAL, GDF1 and GDF3 to their signaling receptors and activation of downstream SMAD2/3 signaling [ 17 , 18 , 19 ]. Additionally, CRIPTO has also been reported to attenuate signaling by other TGF-β superfamily members, namely ACTIVIN A, ACTIVIN B and TGF-β1 and downstream SMAD2/3 signaling through distinct mechanisms ( Figure 1 ) [ 20 , 21 , 22 ].…”
Section: Rise and Fall Of Criptomentioning
confidence: 99%
“…It is generally accepted that TGF-β acts as a multifunctional cytokine and central mediator in the pathogenesis of fibrosis, making it an attractive therapeutic target [ 19 ]. However, the pleiotropic and multifunctional effects of TGF-β and its critical role in normal tissue homeostasis, immunity, and cellular decision-making have raised serious concerns about potential side effects that may be caused by systemic TGF-β blockade [ 198 ].…”
Section: Cripto In the Clinicmentioning
confidence: 99%
“…BMP4 and ActA are both ligands to the TGFβ superfamily. BMP4 binds to BMP type II receptor (BMPR2) and several BMP type I receptors (BMPR1A (or Alk3), BMPR1B (or Alk6) and ACVR1 (or Alk2)), and ActA binds to Activin type II receptors (ACVR2A and ACVR2B) and Activin type I receptors (ACVR1B (or Alk4) and ACVR1C (or Alk7)) [57]. We investigated the expression of the BMP type I receptors and Activin type I receptors and observed that DDX4+ hFGCs in CL0 expressed high levels of BMPR1B, whereas ACVR1B was expressed by all types of hFGCs (Figure 5F).…”
Section: Gene Expression Single Cell Rna Sequencing Analysismentioning
confidence: 99%